2021
DOI: 10.1002/jper.20-0792
|View full text |Cite
|
Sign up to set email alerts
|

Role of thin gingival phenotype and inadequate keratinized mucosa width (<2 mm) as risk indicators for peri‐implantitis and peri‐implant mucositis

Abstract: Background: There is growing evidence on the impact of thin gingival phenotype (TnP) and inadequate keratinized mucosa width (KMW <2 mm) around dental implants on peri-implant health. This study investigated the role of TnP and inadequate KMW (<2 mm) as risk indicators for peri-implantitis and mucositis and on dental patient-reported outcomes. Methods: Sixty-three patients with 193 implants (mean follow-up of 6.9 ± 3.7 years) were given a clinical and radiographic examination and a questionnaire to assess pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 47 publications
(63 reference statements)
2
43
0
3
Order By: Relevance
“…Peri-implant keratinized mucosa has been linked to lower patient esthetic satisfaction and a thicker mucosa can prevent mucosal recession and promote greater stability of interproximal marginal bone levels. Gharpure et al [30] concluded that thin gingival phenotype and inadequate keratinized mucosa width (<2 mm) could be risk indicators for peri-implant disease and pain/discomfort during brushing.…”
Section: Discussionmentioning
confidence: 99%
“…Peri-implant keratinized mucosa has been linked to lower patient esthetic satisfaction and a thicker mucosa can prevent mucosal recession and promote greater stability of interproximal marginal bone levels. Gharpure et al [30] concluded that thin gingival phenotype and inadequate keratinized mucosa width (<2 mm) could be risk indicators for peri-implant disease and pain/discomfort during brushing.…”
Section: Discussionmentioning
confidence: 99%
“…28 More recent data demonstrated that implant sites with thin soft-tissue phenotypes (ie, a reduced horizontal thickness) were more frequently diagnosed with peri-implant mucositis and peri-implantitis compared with control sites (ie, implants with a thick soft-tissue phenotype). 32 The beneficial effect of simultaneous soft-tissue volume grafting employing autogenous connective tissue grafts on the maintenance of peri-implant tissue health and stability has also recently been demonstrated in a cross-sectional analysis. 33 These preliminary findings imply that the vertical and horizontal dimensions of the mucosa may be regarded as crucial structural components for the maintenance of peri-implant tissue health.…”
Section: The Emerg Ing Rele Van Ce Of Peri -Impl Ant Sof T-tissue Dim...mentioning
confidence: 98%
“…In contrast, vertical soft‐tissue thickening resulted in a reduced marginal bone loss over time 28 . More recent data demonstrated that implant sites with thin soft‐tissue phenotypes (ie, a reduced horizontal thickness) were more frequently diagnosed with peri‐implant mucositis and peri‐implantitis compared with control sites (ie, implants with a thick soft‐tissue phenotype) 32 . The beneficial effect of simultaneous soft‐tissue volume grafting employing autogenous connective tissue grafts on the maintenance of peri‐implant tissue health and stability has also recently been demonstrated in a cross‐sectional analysis 33 .…”
Section: The Emerging Relevance Of Peri‐implant Soft‐tissue Dimensionsmentioning
confidence: 99%
“…Patients with TNP exhibited a 27% occurrence of PI compared to the group exhibiting thicker KT of 11.3%. The prevalence ratio of 3.18 between TNP and inadequate KT indicates that "thin tissue phenotype and inadequate keratinized tissue are highly associated" and when both factors are present the incidence of PI may be increased (45).…”
Section: Tissue Phenotype and Ktmentioning
confidence: 99%